Evolution of Unfair Trade Practices in India: Legislative and Judicial Responses (1990–2022) - Shah, Nikhil; Choudhury, Sanjaya (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In this research paper, I have thoroughly described about the topic “Evolution of Unfair Trade Practices in India: Legislative and Judicial Responses (1990–2022).” Unfair practice in the trade sector in India drastically modified from 1990 to 2022. This is an indication of the enhanced level of laws and courts which has helped to uphold the customers as well as ensure fair competition in the market. The CPA 1986 established a means through which unethical business practices could be handled. However, India's attitude to unfair trade practices started to change when the economy became more open in the early 1990s. Monopolies and Restrictive Trade Practices (MRTP) Act of old was scrapped for the Competition Act of 2002. It was aimed at ending anti-competitive action and establishing guidelines for deals. The courts have in its landmark decisions such as Tata Press Ltd v/s Mahanagar Telephone Nigam Ltd (1995) and Indian Medical Association v. V.P. Shantha & Ors. (1995) protected the consumer rights. The Competition Commission of India (CCI), which was established in 2003, makes the competition law even stricter; prevents the large companies from doing some unfair things. In 2019, the CPA was amended and expanded the interpretation of unfair trade practices and introduced new rules on unfair contract and product liability. More changes in regulations were brought forth due to the upsurge of e-commerce and digital communications. Even with such improvement, it is difficult to enforce laws and make them relevant to new issues such as cybercrime and data breaches. Recent changes in India's laws and courts show that the country is serious about meeting global standards and protecting consumers in a market that is changing quickly.